THE PEDAGOGICAL FOUNDATIONS OF INDIVIDUALIZED INSTRUCTION AND THE ESSENCE OF LEARNER-CENTERED APPROACHES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This paper explores the integration of artificial intelligence (AI) frameworks in crafting tailored educational pathways for English language instruction. It highlights the capacity of these systems to diagnose student-specific traits, customize instructional content, track academic growth, bolster learner engagement, and refine the pedagogical strategies employed by educators.